Influence of Zr addition on the corrosion behavior of biomedical PIM Ti-16Nb alloy in SBF - GÜLSOY, HAMİT ÖZKAN (CARL HANSER VERLAG, 2019)
In this study, the effect of Zr content on the corrosion resistance of Ti-16Nb alloy produced by powder injection molding was investigated. Electrochemical corrosion tests were carried out in simulated body fluid using electrochemical impedance spectroscopy and polarization curve analysis. It is observed that, with the addition of 10 wt.% Zr to the base alloy, the corrosion current density and the corrosion rate decreased from 2.23 to 1.55 mu A cm(-2) and 961.7 x 10(-3) mpy to 703 x 10(-3) mpy, respectively. As a result, the addition of Zr has been effective in increasing the corrosion resistance of the Ti16Nb alloy.
Keywords: TiNbZr alloys; Powder injection molding; Electrochemical impedance spectroscopy; Polarization curves; MICROSTRUCTURE